Yemen and education: Shaping bottom-up emergent responses around tribal values and customary law. Issue 3 (20th August 2018) - Webb, Carol
Abstract : Purpose: The purpose of this paper is to draw from up-to-date reports that outline the current situation for Yemen in terms of education and the socio-political context, and to address this context with theory from the complexity science domain in order to propose practical recommendations. Design/methodology/approach: The paper outlines highlights from the current situation in Yemen, namely, the challenges presented by conflict, and international engagement in conflict, and offers an appraisal of key factors pertaining to education and progress made in this arena in recent years. A focus is made on tribal groups as a starting point for bottom-up emergent engagement, and complexity science is suggested as a theoretical domain to draw from to conceptualise how to enact this. Findings: A discussion of how complexity science could be meaningfully applied to the case of education in Yemen is presented, along with seven recommendations for the focus of future international aid interventions in Yemen. Originality/value: At this time, there are few, if no, other works that have been found that have considered the case of education in Yemen in this way from the perspective of a bottom-up emergent engagement with tribes as a way of leveraging the values-based system of tribal customary law in order to address sustainability development goals, literacy, integration in digital society and education as a means of approaching these issues.